Reliability of the Suchey-Brooks method for a French contemporary population. (September 2016) - Savall, Frédéric; Rérolle, Camille; Hérin, Fabrice; Dédouit, Fabrice; Rougé, Daniel; Telmon, Norbert; Saint-Martin, Pauline
Abstract: The Suchey-Brooks method is commonly used for pubic symphyseal aging in forensic cases. However, inter-population variability is a problem affected by several factors such as geographical location and secular trends. The aim of our study was to test the reliability of the Suchey-Brooks method on a virtual sample of contemporary French males. We carried out a retrospective study of 680 pubic symphysis from adult males undergoing clinical Multislice Computed Tomography in two hospitals between January 2013 and July 2014 (Toulouse and Tours, France). The reliability of the Suchey-Brooks method was tested by the calculation of inaccuracy and bias between real and estimated ages, and the mean age for each stage and the mean stage for each 10-years age interval were compared. The degree of inaccuracy and bias increased with age and inaccuracy exceeded 20 years for individuals over 65 years of age. The results are consistent with an overestimation of the real age for stages I and II and an underestimation of the real age for stages IV, V and VI. Furthermore, the mean stages of the reference sample were significantly lower for the 14–25 age group and significantly higher for individuals over 35 years old. Age estimation is potentially limited by differential inter-population error rates between geographical locations. Furthermore, the effects of secular trends are also supported by research in European countries showing a reduction in the age of attainment of indicators of biological maturity during the past few decades. The results suggest that the Suchey-Brooks method should be used with caution in France. Our study supports previous findings and in the future, the Suchey-Brooks method could benefit from re-evaluation of the aging standards by the establishment of new virtual reference samples.